Energetyka wodna w Pakistanie. Szanse i zagrożenia - Głogowski, Aleksander (Polityka i Społeczeństwo, 2020)
Hydro energy is not the main source of energy for the rapidly developing Pakistani economy, but it is an important element of her energy mix. From the Islamabad’s economic interests point of view of, the priority is to limit the scale of black-outs, which slow down the development of economics and make life of Pakistan’s population tougher. Hydro power plants, however, are considered more expensive when it comes to the cost of construction than conventional ones. They have a significant advantage: they do not require fuel, and therefore for a country relatively lacking natural resources it is an interesting alternative. The Indus river basin area is suitable to the construction of this type of infrastructure. However, demographic factors are a serious limitation for the development of this type of infrastructure – the growing population means an increase in the demand for potable water (both for people as well as for the food sector). In addition, environmental risks associated with global warming may also have a negative impact on water supply. International environment is disadvantageous to the development of hydro plants. The Indus Water Treaty, signed with India in 1960, does not match the new challenges posed by both the growing population and the development of hydropower. Therefore, competition in the management of shrinking water resources may lead to an escalation of the conflict between India and Pakistan, lasting over 70 years. An important role for the dynamics of international relations in South Asia, also in the energy and water dimension, has and will have a policy of the People’s Republic of China, which is focused on close cooperation with Pakistan, which is considered by India as a thread.